Semiconducting Carbon Nanotube-Based Nanodevices for Monitoring the Effects of Chlorphenamine on the Activities of Intracellular Ca2+ Stores - Viet Anh Pham Ba; Ngoc Pham Van Bach; Thien Nguyen Luong; Khoa Viet Nguyen (Journal of Analytical Methods in Chemistry)
We report a flexible and noninvasive method based on field-effect transistors hybridizing semiconducting single-walled carbon nanotubes for monitoring the effects of histamine on Ca2+ release from the intracellular stores of a nonexcitable cell. These nanodevices allowed us to evaluate the real-time electrophysiological activities of HeLa cells under the stimulation of histamine via the recording of the conductance changes of the devices. These changes resulted from the binding of histamine to its receptor type 1 on the HeLa cell membrane. Moreover, the effects of chlorphenamine, an antihistamine, on the electrophysiological activities of a single HeLa cell were also evaluated, indicating that the pretreatment of the cell with chlorpheniramine decreased intracellular Ca2+ release. Significantly, we only utilized a single nanodevice to perform the measurements for multiple cells pretreated with various concentrations of chlorphenamine. This enabled the statistically meaningful analysis of drug effects on cells without errors from device variations. Obtained results indicated the novel advantages of our method such as real-time monitoring and quantitative capability. Our devices, therefore, can be efficient tools for biomedical applications such as electrophysiology research and drug screening.